3D PRINTING OF RENAL ARTERY ANEURYSMS. A NEW IMAGING METHOD IN THE THERAPEUTIC DECISION? - Bartikian, Michael (2021)
Case report of a female patient with a right renal artery aneurysm with involvement of distal branches. The angio-CT was diagnostic and showed the anatomy. The arteriogram showed the medial fibrodysplasia pattern but did not add to the tridimensional assessment of the branches. Angio-CT 3D printing allowed for better understanding of the anatomy, valuable for surgical decision and planning which consisted in ex-vivo reconstruction of renal artery which is patent at 1 year follow-up.